2014
DOI: 10.1021/ja500071k
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Cycloaddition of Münchnones onto [60]Fullerene: Organocatalysis versus Metal Catalysis

Abstract: Novel chiral catalytic systems based on both organic compounds and metal salts have been developed for the enantioselective [3 + 2] cycloaddition of münchnones onto fullerenes and olefins. These two different approaches proved to be efficient and complementary in the synthesis of optically active pyrrolino[3,4:1,2][60]fullerenes with high levels of enantiomeric excess and moderate to good conversions. Further functionalization of the pyrrolinofullerene carboxylic acid derivatives has been carried out by esteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(30 citation statements)
references
References 63 publications
0
30
0
Order By: Relevance
“…An appropriate chemical functionalization of graphene addresses the abovementioned challenges tuning the structural, physical, chemical and electronic properties of graphene to suit specific applications. 4 The 4,4-dimethyl-5-oxazolone was studied in industry for many years by groups at 3M, Polaroid, Rohm and Haas GmbH; recently, 4,4-disubstituted azlactones have been used as a way to modify polymer surfaces. 3 Recently, they were employed as mesoionic azomethine ylides in the functionalization of carbon nanomaterials such as fullerenes and carbon nanotubes.…”
mentioning
confidence: 99%
“…An appropriate chemical functionalization of graphene addresses the abovementioned challenges tuning the structural, physical, chemical and electronic properties of graphene to suit specific applications. 4 The 4,4-dimethyl-5-oxazolone was studied in industry for many years by groups at 3M, Polaroid, Rohm and Haas GmbH; recently, 4,4-disubstituted azlactones have been used as a way to modify polymer surfaces. 3 Recently, they were employed as mesoionic azomethine ylides in the functionalization of carbon nanomaterials such as fullerenes and carbon nanotubes.…”
mentioning
confidence: 99%
“…On the other hand, addition of excess Et 3 N (50 mol%) to 2 resulted in higher yield and lower ee as compared with the case when an equimolar amount of Et 3 N (20 mol%) was used (Table 1, entry 19 vs 4), thus suggesting background reaction with Et 3 N. Within that, blank experiments were also performed between acetone and 4-nitrobenzaldehyde using Et 3 N (20% mol) in the absence of organocatalyst and found that no reaction observed in DMSO, while the racemic product 13a was formed in low and moderate yield in DCM and H 2 O, respectively (Table 1, entries [20][21][22]. Therefore, it is verified that background reaction by Et 3 N occurs, which is solvent dependent.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the novel structure and chemical reactivity of fullerenes, it was only recently that C 60 participated as a substrate in an asymmetric cycloaddition reaction of racemic α-allenoates, where chiral phosphines were employed as nucleophilic organocatalysts to yield chiral cyclopentene rings fused onto C 60 [21]. In addition, lately, two strategies for the enantioselective [3þ 2] cycloaddition onto fullerene were reported, namely, the [3þ2] cycloaddition of azlactones onto C 60 representing the first organocatalytic example where oxazolones are employed as 1,3-dipoles with C 60 and the [3þ2] cycloaddition of munchnones on C 60 [22]. However, incorporation of C 60 as integral part of an organocatalyst yet awaits exploration.…”
Section: Introductionmentioning
confidence: 99%
“…Because Prato's reaction is a well‐established methodology for the synthesis of chemically stable pyrrolidinofullerenes, we decided to apply this reaction to support the thiourea moiety on [60]fullerene. Pyrrolidinofullerenes have been prepared by organocatalytic and metal‐catalyzed cycloaddition reactions, but the use of chiral derivatives of C 60 as catalysts has been scarcely studied. Only a few [60]fullerene derivatives complexed to metal atoms have been employed as catalysts, and recently, octahedrally substituted TEMPO–fullerenes [(2,2,6,6‐tetramethylpiperidin‐1‐yl)oxyl–fullerenes] and fullerene–proline hybrids have been used as organocatalysts in the oxidation of alcohols and aldol reactions, respectively.…”
Section: Introductionmentioning
confidence: 99%